2020
DOI: 10.3390/polym12061387
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer Dynamics: A Review of Analytical Theories and Molecular Simulation Methods

Abstract: The theoretical study of dendrimers is reviewed, considering both analytical approaches and molecular simulation methods. We discuss the effect of molecular symmetry on the degeneracy of the relaxation times, and then the calculation of observable quantities, in particular the intrinsic viscosity, and then the viscoelastic complex modulus and the dynamic structure factor, in comparison with the available experimental data. In particular, the maximum intrinsic viscosity with increasing molar mass is analyzed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
(174 reference statements)
0
9
0
Order By: Relevance
“…G Effect of TPP@PAMAM@MA on the cell viability of H9C2 cells (3 independent experiments). H Mitochondrial colocalization of TPP@PAMAM@MA in H9C2 cells (bar, 25 showed that TPP-MR further reduced the sepsis-induced interstitial edema of myocardial cells and better restored the disorder of myocardial fiber arrangement compared with MR (Fig. 8G).…”
Section: Protect Effects Of Tpp-mr On Sepsismentioning
confidence: 96%
See 1 more Smart Citation
“…G Effect of TPP@PAMAM@MA on the cell viability of H9C2 cells (3 independent experiments). H Mitochondrial colocalization of TPP@PAMAM@MA in H9C2 cells (bar, 25 showed that TPP-MR further reduced the sepsis-induced interstitial edema of myocardial cells and better restored the disorder of myocardial fiber arrangement compared with MR (Fig. 8G).…”
Section: Protect Effects Of Tpp-mr On Sepsismentioning
confidence: 96%
“…The targeted drug delivery system (DDS) was a kind of preparation that could introduce drugs into the body and improve the bioavailability and safety by controlling the release rate, time, and position of medicines [ 23 , 24 ]. Dendrimer can encapsulate small molecule drugs through electrostatic force, van der Waals force, and H bond due to its unique properties (such as nanometer uniform hook size, high degree of branching, multivalent state, water solubility, available lumen, and convenient synthesis method) [ 25 ]. Common types of dendrimers include poly lysine (PLL), polypropylene imine (PPI), polyethylene imine (PEI), poly aryl ether, and poly amido amine (PAMAM).…”
Section: Introductionmentioning
confidence: 99%
“…MC methods are a class of techniques based on random sampling to numerically solve problems that have a probabilistic interpretation [ 31 ]. MC methods have broad applications in polymer science [ 32 , 33 , 34 ], especially in polymer reaction engineering [ 28 , 33 ]. Johnson and O’Driscoll [ 35 ] used an MC simulation to study sequence distributions in step-growth copolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the corrosion field, MD simulation also offers numerous advantages in various sectors such as renewable energy generation, food technology, medicine, and pharmaceutical [15][16][17][18]. A broad list of reviews of MD simulation application for corrosion sector as well as other sectors had been published in the literature [14,[19][20][21][22]. In this context, numerous works have shown that MD simulation is a promising method to obtain the molecular level information of a system.…”
Section: Introductionmentioning
confidence: 99%